Coefficient of Congruence: a Proposal for Calculation - Dominguez Lara, Sergio Alexis (Pensando Psicología, 2013)
This paper presents a module in ms Excel to calculate the coefficient of congruence. Its importance and its lack of implementation in traditional statistical packages justify building the tool to support research in psychology, because of the need to compare factor structures with those found in other analyses to determine whether or not they are congruent. The paper also discusses the use of the tool.
Keywords: factor analysis; coefficient of congruence; methodology; psychometrics